Systematic Literature Review: Pengaruh Kepemimpinan Kepala Sekolah dalam Meningkatkan Motivasi dan Kinerja Guru - Sunari Sunari (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to examine the influence of school principals' leadership in enhancing teacher motivation and performance using the Systematic Literature Review (SLR) method. A total of 25 relevant articles were analyzed to identify patterns and key findings. The results reveal that principals play a critical role in creating a conducive school environment that fosters teacher motivation and supports the development of professional competencies. School leadership significantly contributes to improving teacher effectiveness through strategic decision-making, supervision, and collaborative school culture. The review also identifies challenges faced by principals, such as adapting to policy changes and managing diverse teacher characteristics. The key contribution of this study lies in its comprehensive synthesis of theoretical and practical insights, emphasizing the importance of adaptive and collaborative leadership. Additionally, the findings offer valuable policy implications by highlighting the need for leadership development programs that are responsive to the evolving demands of the education system, thus enabling principals to serve as effective role models in improving teaching quality.